Synthesis and characterization of boehmitic alumina coated graphite by sol-gel method - Yilmaz, Suat; Kutmen-Kalpakli, Yasemen; Yilmaz, Ersan (ELSEVIER SCI LTD, 2009)
Non-wettability property makes graphite a good protecting material against the molten metal and/or slag. Properties like high oxidation potential between 600 and 1200 degrees C and non-wettability with water at room temperatures limits the usage of graphite in castable refractory applications. In this study, sol-gel method, which is a relatively cheaper process, was used. Boehmitic sol was obtained by hydrolyzing and peptiziting the alkoxide AIP (aluminum isopropoxide) used as alumina source. Then natural flake graphite was mixed with the boehmitic solution for coating of graphite. At 120 degrees C boehmitic sol coated graphite was dried and gelled. Then heat threaded at 550 degrees C for gamma-Al2O3 transformation of boehmite. Products that obtained from the studies were characterized with FTIR and XRD tests. Alumina coated graphite samples were made by repeating the same steps and TG analysis were made to investigate the oxidation behaviour of the samples. Finally, SEM-EDS analyses were carried out to investigate the microscopic properties of the alumina coated graphite powders. (C) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Sol-gel coating; Alumina; Graphite; TG analysis; OXIDATION RESISTANCE; Materials Science